Underestimation of alleged Rockwood II injuries-Don’t miss horizontal instability - Banerjee, Marc; Spüntrup, Carolin; Lambert, Christophe; Bouillon, Bertil; Wafaisade, Arasch (Sportverletzung · Sportschaden, 2025)
There is broad consensus that Rockwood type II injuries are treated conservatively. However, several studies have shown that some of these patients have persistent mid- to long-term symptoms, partly due to horizontal instability.Patients with a side-to-side difference of up to 25% in the coracoclavicular distance on bilateral stress radiographs were included in this case series if they had either a posterior subluxation of the distal clavicle on axial radiographs and/or on MRI (in 8 patients), or if they showed dynamic posterior instability both clinically and radiologically. Injuries other than Rockwood type II or Rockwood type II injuries without horizontal instability were excluded.During the period from 2015 to 2022, 13 patients with an average age of 30.7 years (range 21–48 years) fulfilled the inclusion criteria. The mean time from trauma to final diagnosis was 32.4 days (range 7–67 days). Eight patients had an additional static posterior dislocation of the distal clavicle consistent with a Rockwood type IV injury. Five patients had dynamic posterior instability. All patients had initially been classified as having Rockwood type II injuries based on the findings of bilateral stress radiographs at the referring institution.The diagnosis of a Rockwood type II injury should not be based solely on bilateral stress radiographs but should instead be made only after horizontal instability has been ruled out with appropriate imaging modalities. Otherwise, Rockwood type IV injuries or Rockwood type II injuries with concomitant horizontal instability may be overlooked.
Keywords: Acromio-clavicular joint separation; horizontal instability AC joint; dynamic horizontal instability AC joint; Rockwood II injur